Concise synthesis of 23-hydroxylated vitamin D3 metabolites. Issue 186 (February 2019) - Kawagoe, Fumihiro; Sugiyama, Toru; Yasuda, Kaori; Uesugi, Motonari; Sakaki, Toshiyuki; Kittaka, Atsushi
Graphical abstract: Highlights: CYP24A1 metabolites of 25-hydroxyvitamin D3 were efficiently synthesized. The Claisen condensation was used for the 23, 25-dihydroxyvitamin D3 metabolite. 23, 25, 26-Trihydroxyvitamin D3 was synthesized using Grignard reaction. Abstract: Three 23-hydroxylated vitamin D3 derivatives, which are metabolites of 25-hydroxyvitamin D3 produced by CYP24A1 and a related diastereomer, were efficiently synthesized. Each C23 hydroxy unit was constructed by the Claisen condensation reaction with ethyl acetate or the Grignard reaction with 2-methylallymagnesium chloride. Stereochemistry at the C23 position was determined by a modified Mosher's method. The triene structures were constructed by the Wittig-Horner reaction utilizing the A-ring phosphine oxide moiety.